"The queen stays queen, adios" the impact of editing on the legacies of women winners of color on Survivor (2000-2022) - Vesliño, Matthew Lorenzo Dimagiba
This study interrogates the narrative faculties of editing for reality television, in particular its capacity to reflect various realities through results-oriented storytelling. Specifically, this critiques the editing of the competitive reality television series, Survivor (2000–) and how the editing of its women winners of color impact the stories of their respective successes. In order to develop a more comprehensive understanding of how editing for competitive reality television is intentional in its weaving of narratives for successful individuals with marginalized identities, this study employs the fan-made, formalist framework of Edgic as explored by Holmes (2015) and Lindbergh (2020), while grounded by Crenshaw's (1991) lens of representational intersectionality to understand the ways in which intersectional hegemony pervaded their media representations on Survivor. This study finds that the editing logic of Survivor ultimately underrepresented, undervalued, and undersold the legacies of these women winners of color as subordinate to their white and/or male competitors, even when their multidimensional stories were far more nuanced than their edited portrayals had made them seem.